日本放射線技術学会の海外派遣事業における派遣者の動向および業績の調査 - 松原, 孝祐; 田中, 利恵; 小倉, 明夫; 有村, 秀孝; (2015・2016, 年度国際戦略委員会); 辻岡, 勝美; 宮地, 利明; 小林, 正和; 上田, 克彦; 森岡, 茂晃 (Nippon Hōshasen Gijutsu Gakkai zasshi, 2017)
Japanese society of radiological technology (JSRT) categorizes three international delegation projects; short-term studying abroad program (STSAP), international academic society visit program (overseas) (IASVP), and international internship visit program (Stanford University) (IIVP) for driving globalization of JSRT. In this survey, we conducted a questionnaire evaluating effectiveness of the international delegations. The survey covered 50 delegates of STSAP, 180 delegates of IASVP, and 100 delegates of IIVP. This survey includes detailed histories of career, current position, academic articles, and presentations as a first presenter before and on, and after each program. We categorized into six groups (change career, promoted in a position in hospital, kept a current position in hospital, promoted in a position in university, kept a current position in university, and others) in three programs. The response rate is approximately 58% (191/330 delegators). In all programs, almost all the delegates were radiological technologists in the hospital. They had reported a lot of academic articles and made a lot of presentations, and promoted in the hospital and/or university. STSAP, IASVP and IIVP were descending order of the average number of the articles as a first author and presentations as a first presenter. They published more the academic articles in Japanese than in English compared to JJRT and RPT. Therefore, research achievements and human resource conducted by this project provide great technologists and technique, and education. For further JRST globalization, it is desirable that we can continue these international delegations and verify the effectiveness.